Prevalence, risk factors and association of renal artery stenosis with coronary artery disease in patients undergoing coronary angiography in Ibn-Al Bitar center for cardiac surgery - Khalaf, Khalil S.; Haji, Ghazi F.; Mahmood, Ghassan M.; Quraishi, Muthanna Al- (Journal of the Faculty of Medicine Baghdad, 2017)
Background:-Atherosclerosis is a systemic disease that often affects multiple vascular distributions in a single patient. The increased prevalence of renal artery stenosis in association with coronary artery disease has been well documented.Objectives:-To examine in detail the prevalence of renal artery stenosis in patients undergoing cardiac catheterization for suspected coronary artery disease.Patients &methods:-Between April 2010 and February 2011, two hundred patients underwent coronary and renal angiography at the same session in Ibn Al-bitar Hospital for Cardiac Surgery. Clinical and procedural data for patients undergoing renal angiography were prospectively collected and entered into database specially designed for the present study.Results:-Two hundred patients were included in this study, 133 (66.5%) were males and a mean age of 53±12 years, age range (42-73 year). Significant renal artery stenosis (≥ 50% luminal narrowing) was identified in 18 patients (9%) made up the renal artery stenosis group. Age, hypertension, diabetes mellitus and renal impairment were significantly associated risk factors for renal artery stenosis. Gender, smoking and hyperlipidemia were not significantly associated with either group. The frequency of renal artery stenosis is significantly increased with the number of stenotic coronary segments; patient with two and three vessel disease had more frequent renal artery stenosis than the others.Conclusion:-Renal artery stenosis is prevalent in a significant proportion of patients undergoing cardiac catheterization for suspected coronary artery disease & the number of coronary arteries with stenotic lesions is a remarkable predictor of significant renal artery stenosis.